Imposing Sanctions on School Students in East Kolaka, Indonesia: Perspectives of Islamic Law and Islamic Education - Herman, Herman; Ilham, Muhammad; Pratama, Finsa Adhi; Kartini, Kartini; Iqbal, Muhammad (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
Education has become one of the fundamental human rights that must be fulfilled by the state and implemented through legislation. The right to a good education for all citizens has become a global discourse, alongside the rights to work, freedom of speech, and a decent social life. This study examined the imposition of sanctions on students in schools in East Kolaka, Southeast Sulawesi. The study concerned with the perspectives of Islamic law and Islamic education towards imposing sanctions on school students. The study used a qualitative method, analyzed with Islamic law and Islamic education theories. Data were collected by means of observation and in-depth interview with school principal, teachers, students, and academics. The findings reveal that schools apply disciplinary measures as part of the strategies to enforce school code of conduct. Schools integrate such measures into daily activities, which include providing guidance, setting a good example in words and deeds, applying sanctions, and providing rewards. In the view of Islamic law, the imposition of sanctions on students in educational institutions has benefits and is in line with the concept of maqashid al-sharia to discipline students and build their character from a young age, thereby producing good morals. Further, in the perspective of Islamic education, obedience, discipline, and respect for teachers are the morals of students that will have an intellectual and spiritual impact until they reach adulthood.